2010
DOI: 10.1577/m09-149.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Drifting Pallid Sturgeon Larvae in the Missouri River Inferred from Two Net Designs and Multiple Sampling Locations

Abstract: Nearly 430,000 larval pallid sturgeon Scaphirhynchus albus (5-13 d posthatch) were released in the Missouri River and allowed to free-drift for 5.7 km and then were sampled at a river bend by boats positioned on the inside-bend, inside-bend channel border, mid-channel, and outside-bend locations of the channel. Boats were rigged with conical nets and rectangle nets designed to sample for drifting pallid sturgeon larvae along the bottom and at the surface of the river to address three objectives: (1) examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…Even during high water, these structures may limit age-0 sturgeon access. For example, the majority of free-embryo sturgeon drift is near the bottom (Braaten et al 2008(Braaten et al , 2010, thus, even when these inlet control structures are overtopped during high water, young sturgeon may not be capable of successfully drifting over these structures. Woodward and Rus (2011) found that chute inlet control structures limited the amount of Missouri River course-grained suspended sediment entering Upper Hamburg and Glovers Point chutes, demonstrating the potential barrier that these structures may pose to other objects drifting near the bottom, such as sturgeon larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Even during high water, these structures may limit age-0 sturgeon access. For example, the majority of free-embryo sturgeon drift is near the bottom (Braaten et al 2008(Braaten et al , 2010, thus, even when these inlet control structures are overtopped during high water, young sturgeon may not be capable of successfully drifting over these structures. Woodward and Rus (2011) found that chute inlet control structures limited the amount of Missouri River course-grained suspended sediment entering Upper Hamburg and Glovers Point chutes, demonstrating the potential barrier that these structures may pose to other objects drifting near the bottom, such as sturgeon larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Stage-specific peculiarities in (active) spatial dispersal cannot be derived from DIFF alone; drift patterns where younger individuals concentrate near the bank and older ones in mid-channel , or vice versa (Braaten et al 2010), could remain concealed. Such characteristics are revealed in the unequal distribution of L2 and L4 nase over the sampling area (i.e., in particular drift nets), potentially originating from differences in behaviour, orientation, and swimming.…”
Section: Developmental Stagementioning
confidence: 99%
“…groyne fields; Lechner et al 2014a) or be concentrated in dead zones, slackwater habitats (Wolter and Sukhodolov 2008;Kopf et al 2014) and concave riverbanks (Pavlov et al 2008). Depending on discharge levels, hydraulic forces may concentrate young fish in areas with high current speeds, such as the thalweg (Braaten et al 2010;Ellsworth et al 2010a). If larvae are kept in suspension under high discharges, this may considerably increase drift distance and influence longitudinal distribution patterns (Corbett and Powles 1986).…”
Section: Passive Driftmentioning
confidence: 99%
“…This information can elucidate patterns and processes associated with spawning and larval production (Zitek et al 2004a;King et al 2005;Braaten et al 2010;Borcherding et al 2014), it may allow forecasting of future year-class-strength (Johnston et al 1995) and provide estimates of stock size of spawning adults (Usvyatsov et al 2013). It also assists in understanding how fishes and their environmentespecially the flow environment-interact.…”
Section: Introductionmentioning
confidence: 99%